A Bench Scale Comparison of Batch and Continuous Settling - Heffler, Howard Russell (My University, 1971)
A bench scale continuous settling unit was constructed and its operation compared to results of batch settling tests. The particulate solids used were polystyrene spheres with a mean diameter of 285 microns. The concentration profile within the slurry in both the batch and the continuous studies was observed using a light extinction technique.
The results show that for the material used in this study, the solids flux limitation of the continuous settler could not be exceeded: the limiting condition in the operation was always the clarification capacity or upward velocity. The batch flux plot shows that this will be the case for any material which exhibits a flux plot that is essentially a single concave curve downwards.
Keywords: bench, scale, comparison, batch, settling